N-tosylhydrazones as acceptors for nucleophilic alkyl radicals in photoredox catalysis: A short case study on possible side reactions. Issue 3 (1st February 2022) - Kinsella, Anna G.; Tibbetts, Joshua D.; Stead, Darren; Cresswell, Alexander J.
Abstract: We report the attempted development of a photoredox-catalyzed α-C–H alkylation reaction of aliphatic amine derivatives, using N -tosylhydrazones as radical alkylating partners. The original intention was to intercept α-aminoalkyl radical intermediates with N -tosylhydrazones, followed by the expulsion of a sulfonyl radical by β-scission to generate N -H diazene species. Facile denitrogenation of these intermediates would remove all traces of the hydrazone moiety and provide a net C–H alkylation process. However, our plans were derailed by issues with the low reactivity of N -tosylhydrazones toward intermolecular capture by nucleophilic radicals, and several unexpected side reactions. Our findings, though unsuccessful, do serve to identify challenges for future researchers attempting to develop similar transformations. Graphical Abstract: UF0001